2019
DOI: 10.3389/fmats.2019.00175
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Composition-Structure Relations in Alkali Borosilicate Glasses Using Statistical Mechanics

Abstract: Predicting the atomic-scale structure of multicomponent glasses from their composition and thermal history would greatly accelerate the discovery of new engineering and functional glasses. A statistical mechanics-based approach has recently been applied to predict the composition-structure evolution in binary oxide glasses by determining the relative entropic and enthalpic contributions to the bonding preferences. In this work, we first establish the network modifier-former interaction parameters in sodium sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…The structure of the present silicate and borate glasses are predicted using a statistical mechanics model [38] based on existing 29 Si and 11 B magic angle spinning (MAS) NMR spectroscopy data for other compositions [20,39]. The silicate network becomes increasingly depolymerized with increasing cesium content visible by the decrease in Q 4 species (Supplementary Figure S1) and, thus, an increase in Q 3 species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the present silicate and borate glasses are predicted using a statistical mechanics model [38] based on existing 29 Si and 11 B magic angle spinning (MAS) NMR spectroscopy data for other compositions [20,39]. The silicate network becomes increasingly depolymerized with increasing cesium content visible by the decrease in Q 4 species (Supplementary Figure S1) and, thus, an increase in Q 3 species.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the boron and phosphorus containing glasses are new compared to the original study [7]. The number of bridging oxygens is either taken directly from the reference, calculated from NMR data (Q n or B 3/4 units) if available (these describe whether the oxygen bonded to a Si unit or B unit is bonded to another Si/B or is an ionic oxygen charge balanced by modifier ions), predicted from statistical modelling (as described in Figure 1 and Supplementary Figures S1 and S2) [38,65], or estimated as Equation (7),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, from the statistical mechanics model 53 for the considered structural transitions. Explicit details of the calculations are extensive and can be found in previous works by Bødker et al 53,65,66 The first transition outlined, Q 4 N 6 , is the → baseline transition which was used for normalization. 19 showing that the increase in N 6 units occurs only until about 20% modifier oxide (x), after which it continuously decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In order to calculate the H i model parameters based on the relevant structural evolution, a Python script was developed based on a basin-hopping algorithm which determines the global minimum in the error between the fit and the experimental values. Further details can be found in the extensive works of Bødker et al 53,65,66 Due to the difficulty of using NMR spectroscopy to study germanate glasses, the model was not fit to experimental NMR data, but rather fitted to the proposed structural model by Kiczenski et al 19 shown in Figure 1. It is worth noting that this structural model is, in turn, based on the experimental work of Jain et al 40 for the rubidium germanate system.…”
Section: Author Manuscriptmentioning
confidence: 99%